Characteristics of Entropion Patients at Dr. Mohammad Hoesin General Hospital: A Descriptive Study - Tresa Ivani Saskia; E Iskandar (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2022)
Introduction: The eyelids or lids have the function of protecting the eyeball and secrete glandular secretions that form a tear film in front of the cornea. This study aimed to assess the characteristics of patients with entropion. Methods: This research is a retrospective study approach. Data was obtained from Dr. Mohammad Hoesin General Hospital, Palembang, from January 2019 to December 2021. Medical record data included in this study were patients diagnosed with ptosis, entropion, and ectropion patients. The exclusion criteria were patients with missing medical records and any other palpebra abnormalities. The necessary variables were analyzed descriptively by calculating the prevalence and looking at the patient characteristics of entropion. Results: Most age in patients with entropion are those with age >60 years, which is as much as 66.67% of patients. The most affected eyes were the left eye and both eyes (44.44%) and the superior eyelid (66.67%). In this study, the most common type of entropion was the cicatricial type which was found in 5 patients (55.56%). No spastic and congenital entropion was found in this study. Conclusion: The most common age are those with age >60 years. The cicatricial type was the most common type in patients with entropion at Dr. Mohammad Hoesin General Hospital.